Marketing mix standardization: a cross cultural study of four countries - Kustin, Richard Alan (International Business Review, 2004)
The study researched the possibility of standardizing the marketing mix by investigating the cross-cultural responses from the United States, Brazil, France and India. The study tested the premise of standardization by determining if respondents perceived specific attributes of a common non-durable consumer product the same or differently. The results indicate the opportunity for dynamic marketing standardization remains limited but applicable within specific cultural country markets. Several attribute perceptions between US and foreign respondents are found to be more similar than dissimilar suggesting advantages may exist for a limited implementation of marketing mix standardization as part of a global marketing strategy. © 2004 Elsevier Ltd. All rights reserved.
Keywords: Consumer product; Cross-culture; Globalization; Hofstede; International marketing; Marketing mix; Standardization; dept.mkt